Effective EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF - FAJAR BUDIYONO (STKIP PGRI SUMENEP, 2021)
Problem based learning is a learning model to demannd for the students in improving creative thinking, critical thinking and high order thinking. In problem based learning, the problem must be contextual. The research is qualitative. The methode is literatur review. The data were from references, textbook, and journals. The result showed that (1) the problem based learning was designed to improve creative thinking (2) by the problem, the students could observe the adult role in contextual. Then, the students could be independently and autonomous students.